Novel comonomer synthesis from thiophene-2-carbonyl chloride and polydimethyl siloxane modified cyclohexanone formaldehyde resin. Issue 5 (19th August 2014) - Kizilcan, Nilgun; İstif, Merve
Abstract : Purpose: The purpose of this paper is to produce an electro active monomer containing ketonic resins and then to investigated redox reaction between Fe+3 and bounded thiophene in comonomer. Firstly, thiophene functionalised ketonic resins (Th–CFPDMSR) were synthesised by esterification reaction of thiophene-2-carbonyl chloride (ThCCl) and hydroxyl groups of CFR. Th –CFPDMSR was then polymerised by ferric salt. This, thiophene modified ketonic resins (Th-CF-PDMSR) as comonomers were characterised by common techniques such as Gel Permeation Chromatography (GPC), 1H-NMR, Fourier Transform Infrared (FTIR-ATR) spectroscopy, Differential Scanning Calorimeter (DSC), and Scanning Electron Microscope (SEM). Design/methodology/approach: Th-CFPDMSR comonomers were synthesised by esterification reaction of thiophene-2-carbonyl chloride (TCCl) and hydroxyl groups of ketonic resins. Then, the in situ chemical oxidation (ICO) of ThC-CFR in the presence of iron (III) chloride salt (FeCl3) was accomplished in chloroform (CHCl3) / acetonitrile mixture (ACN) solutions at room temperature Findings: Important structural factors determined quantitatively for Th–CFPDMSR is the CFPDMS / TCCl ratio after reaction. The mole ratio effect of TCCl and ketonic resin, on the solubility, molecular weight, Tm and Tg values of the comonomers (TCCl-CFPDMSRs) were investigated. Research limitations/implications: The ferric ion (Fe+3) has a standard oxidation potential. Furthermore, FeCl3 can react with thiophene to produce a cation radical. FeCl3 can not react with hydroxyl groups of ketonic resins. When ferric is used for in situ chemical oxidation (ISCO) application at relatively low temperatures (e.g., <20 °C), the oxidation reactions are usually less aggressive. Practical implications: This work provides technical information for the synthesis of conducting block copolymer and for the synthesis of chain extended resins. The modified resins contain thiophene. The chemical oxidation system has been used to polymerise these thiophene groups and resins with much higher molecular weight might be produced. The resins may also promote the adhesive strength of a coating and corrosion inhibition to metal surfaces of a coating. Originality/value: Novel Th-CFPDMSR comonomers were synthesised. These comonomers have higher Tg and Tm value than CF-PDMSR alone. The chemical oxidation system has been used to polymerise these thiophene functionalized ketonic resins.